60 RELATIONSHIP BETWEEN PRIMARY CARE ACCESS AND PEDIATRIC INJURY AND POISONING: AN ANALYSIS OF THE 2003 NATIONAL HEALTH INTERVIEW SURVEY. (1st March 2006) - Ryan, L. M.; Freishtat, R. J.; Simon, S. D.; Sharma, V.; Wright, J. L.
Abstract : Background: Primary care access is associated with better health and lower costs of care; its effect on injury risk has not been evaluated. Although not consistently demonstrated, positive outcomes associated with primary care injury counseling have been shown. The American Academy of Pediatrics identifies preventive counseling as a priority during well-child visits. Despite this, injuries remain the leading cause of pediatric morbidity and mortality. Is this an effect of inadequate access to primary care services? Design/Methods: Data from the Child Health Care Access and Utilization section of the Sample Child Core of the 2003 National Health Interview Survey (NHIS) were analyzed to identify children with limited access to primary care services. Access patterns were determined based on survey responses to indicators of primary care access: usual place of routine/preventive care, usual place of health care, and presence of unmet health care needs. Responses were categorized as limited, partially limited, not limited, and unmet needs. Using multiple logistic regression comparisons, the impact of these limitations on medically attended injury/poisoning rates was evaluated. An adjusted odds ratio of injury as a function of limited primary care access was obtained after controlling for confounders and demographic differences. Results: With control for gender, age, minority status, poverty, and medical insurance, no significant effect of primary care access limitations or presence of unmet health care needs was shown on the proportion of medically attended pediatric injury/poisoning episodes (Table 1 ). Conclusions: Primary care access, as a single variable, is not associated with a significant effect on medically attended injury/poisoning episodes in the pediatric population. Injury risk likely reflects multifactorial contributory circumstances and events.